An interactive self-umrah planner mobile application using android / Wan Nor Khairina Wan Rohaimi - Wan Rohaimi, Wan Nor Khairina (2019)
Nowadays, those who are planning to perform Umrah will have to deal with a travel agent in order to do Umrah. Meanwhile, travel agent tend to provide packages for Umrah Pilgrims in which could not be necessary for those who are already been to Makkah or Madinah before. Besides, they also would face some difficulties in finding an authorized travel agent as they need to approach them for visa purpose. Other than that, it could be troublesome for them in finding each of the hotel and accommodation needed which requires them to look thoroughly throughout the internet. Therefore, the objective for this project is to design a platform which ease the Umrah pilgrims in searching their hotel and accommodation needed by them during Umrah. Other than that, this project have developed a mobile application that can help Umrah pilgrims in creating their own itinerary during their Umrah period. Other than that, an application that centralized all of the authorized travel agents has been develop to ease them throughout the process of visa application. This application is created using Android framework and can be used in an Android-based smartphone. Users are able to plan their own Umrah trip with ease with the guide from this application. Besides, users also able to manage their cost and time effectively by using this mobile application.